Functional characterization of CYP4G11—a highly conserved enzyme in the western honey bee Apis mellifera. Issue 5 (31st July 2018) - Calla, B.; MacLean, M.; Liao, L.‐H.; Dhanjal, I.; Tittiger, C.; Blomquist, G.J.; Berenbaum, M.R.
Abstract: Determining the functionality of CYP4G11, the only CYP4G in the genome of the western honey bee Apis mellifera, can provide insight into its reduced CYP4 inventory. Toward this objective, CYP4G11 transcripts were quantified, and CYP4G11 was expressed as a fusion protein with housefly CPR in Sf9 cells. Transcript levels varied with age, task, and tissue type in a manner consistent with the need for cuticular hydrocarbon production to prevent desiccation or with comb wax production. Young larvae, with minimal need for desiccation protection, expressed CYP4G11 at very low levels. Higher levels were observed in nurses, and even higher levels in wax producers and foragers, the latter of which risk desiccation upon leaving the hive. Recombinant CYP4G11 readily converted octadecanal to n‐heptadecane in a time‐dependent manner, demonstrating its functions as an oxidative decarbonylase. CYP4G11 expression levels are high in antennae; heterologously expressed CYP4G11 converted tetradecanal to n‐tridecane, demonstrating that it metabolizes shorter‐chain aldehydes. Together, these findings confirm the involvement of CYP4G11 in cuticular hydrocarbon production and suggest a possible role in clearing pheromonal and phytochemical compounds from antennae. This possible dual functionality of CYP4G11, i.e., cuticular hydrocarbon and comb wax production and antennal odorant clearance, may explain how honey bees function with a reduced CYP4G inventory.